1995
DOI: 10.1109/20.364673
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on simple railgun with the compacted plasma armature

Abstract: Our objective was to elucidate the physical reasons of the velocity limitation in the plasma armature (PA) railgun at the 6 k d s level. To do this, we have designeda simple system having no vacuum and no preaccelerator. The 1-2 g mass projectile is launched at the maximum possible constant acceleration4he limit of the projectile strength or the electrothermal explosion of rail surfaces, while making use of the effects of the material strengthening under the great confining pressure and rail current redistribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…However, several decades of railgun research showed a persistent velocity ceiling of about 5-6 km/s for plasma-armature launchers. Railgun researchers working in the early 1970s had assumed that plasma armature railguns should be able to achieve exit velocities of tens of kilometers per second; however, they were only able to achieve velocities of 4-5 km/s for medium-bore (25-50 mm) railguns operating at typical accelerations of 400-600 kG [2], [3], and 6-7 km/s in smaller-bore guns operating at 1 MG or greater [4], [5]. These fast accelerations enabled researchers to outrun most of the problems that contribute to the velocity ceiling.…”
Section: Introductionmentioning
confidence: 99%
“…However, several decades of railgun research showed a persistent velocity ceiling of about 5-6 km/s for plasma-armature launchers. Railgun researchers working in the early 1970s had assumed that plasma armature railguns should be able to achieve exit velocities of tens of kilometers per second; however, they were only able to achieve velocities of 4-5 km/s for medium-bore (25-50 mm) railguns operating at typical accelerations of 400-600 kG [2], [3], and 6-7 km/s in smaller-bore guns operating at 1 MG or greater [4], [5]. These fast accelerations enabled researchers to outrun most of the problems that contribute to the velocity ceiling.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers involved in that research were met with a great deal of challenge and difficulty, especially in getting plasma armatures to accelerate payloads to muzzle velocities in excess of 6 km/s at acceleration levels under 1 MG [1]. In those experiments, velocities of only 4-5 km/s were achieved for medium--bore (25-50 mm) railguns operating at typical accelerations of 400-600 kG [2,3], and velocities of 6-7 km/s were achieved in smaller bore guns operating at 1 MG or greater [4,5]. The researchers involved proposed a * corresponding author; e-mail: david wetz@iat.utexas.edu number of theories to account for the velocity ceiling and even proposed a number of solutions that could be used to overcome the obstacles, but no significant effort was put into implementing them.…”
Section: Introductionmentioning
confidence: 99%
“…The problem is mainly the low efficiency of shock heating as the shock wave carries greater part of the impact energy into the target. On the other hand, Shoemaker (1977) and O' Keefe and Ahrens (1977) (Kondo and Ahrens, 1983;Drobyshevski et al, 1990) indicating the presence of overheated gas in such regimes when, by calculations, liquid phase would just appear. The averaged hydrodynamic description obviously fails in such conditions.…”
mentioning
confidence: 99%